Imaginary friend [compact disc, unabridged] - Chbosky, Stephen (Hachette Book Group, 2019)
Single mother Kate Reese and her son Christopher settle in Mill Grove after escaping an abusive relationship. Then Christopher vanishes, and returns six days later with a voice in his head.